Primary (Idiopathic) Non-Pancreatic Retroperitoneal Pseudocyst in a Young Female: A Rare Case Report - Abhay M Philip; Leo F Tauro (Journal of Clinical and Diagnostic Research, 2023)
Retroperitoneal Cysts (RPC) are uncommon, with an estimated incidence of 1 in 5,750 to 1 in 250,000. A 26-year-old woman presented with dull aching, non-radiating pain in the upper abdomen for the past two months, with no aggravating or relieving factors. On clinical examination of the abdomen, a grossly visible mass measuring approximately 10x10 cm with a smooth surface, firm consistency, and well-defined borders was observed in the left lumbar and iliac region. Contrast-Enhanced Computed Tomography (CECT) of the abdomen and pelvis revealed a well-circumscribed cystic lesion measuring 9.3x9.5x5.5 cm in the left lumbar region near the tail of the pancreas. The pancreas appeared normal with no surrounding fat stranding or inflammatory changes. Peripheral enhancement and peripheral wall calcification were observed. The patient underwent laparotomy and cyst excision. Intraoperatively, the cyst was found to arise from the retroperitoneum located in the lesser sac. It was dissected out from the tail of the pancreas, and no obvious communication with the pancreas was observed. The cyst was excised completely. Histopathological examination revealed a cyst with absent endothelium, suggestive of a pseudocyst. Previous literature reports indicate that RPCs are very rare and are often discovered incidentally. Patients may be asymptomatic or present with vague symptoms. Imaging can help diagnose these lesions, but surgery is crucial in confirming the diagnosis.